Development of Teachers’ Emotional Adjustment Performance Regarding Their Perception of Emotional Experience and Job Satisfaction During Regular School Operations, the First and the Second School Lockdown in Austria - Lindner, Katharina-Theresa; Savolainen, Hannu; Schwab, Susanne (Frontiers in Psychology, 2021)
Starting with the COVID-19 pandemic, research intensively investigated the effects of school lockdowns on involved stakeholders, such as teachers, students and parents. However, as research projects had to be hurriedly conducted, in-depth and longitudinal studies are lacking. Therefore, the current study uses data from a longitudinal study to investigate the well-being of Austrian in-service teachers during the COVID-19 pandemic. In total 256 teachers took part at both measurement waves and participated in an online survey. Standardized questionnaires were used to assess teachers’ perception of emotional experiences and job satisfaction before COVID-19 (retrospective, t1), during the first (in situ, t2) and during the second school lockdown (in situ, t3). The results indicated that the vast majority of teachers generally felt a high level of job satisfaction. However, teachers’ satisfaction decreased between regular teaching and school lockdowns. Similarly, positive emotional activation was reduced and negative activation increased. Further, results from a positive activation cross-lagged path model indicated that the lack of positive activation led to lower job satisfaction. For negative emotional activation, job satisfaction during the first school lockdown predicted negative activation at the second lockdown.